Quantitative analysis for CIGS thin films by surface analytical techniques - Kim, Seon Hee; Jang, Yun Jung; Yoon, Jung Hyeon; Jeong, Jeung-hyun; Lee, Yeonhee (WILEY-BLACKWELL, 2014)
The compound semiconductor Cu(In,Ga)Se-2 (CIGS) is well known as the next-generation solar cell material because of its high absorption coefficient for solar radiation, suitable band gap, ability to be deposited on flexible substrate materials, and producing highly flexible and lightweight solar panels. In order to improve the performance of solar cells, a quantitative and depth-resolved elemental analysis of photovoltaic thin films is strongly required. In this study, we determined the average concentration of the major elements, Cu, In, Ga, and Se in fabricated CIGS thin films, using inductively coupled plasma atomic emission spectrometry, X-ray fluorescence, and electron probe microanalysis. Depth profiling results for CIGS samples using AES, XPS, magnetic sector SIMS, and time of flight SIMS were also obtained to compare their atomic concentration results. In the SIMS technique, detection of MCs+ clusters reduced possible matrix effects because of the variant concentrations of In and Ga. The reproducibility and accuracy of quantitative analysis were investigated as a function of ion sputtering energy. The compositional distributions of CIGS absorber layers as measured by MCs+-SIMS showed good agreement with those of AES and XPS. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: SOLAR-CELL DEVICES; ICP-OES; HETEROJUNCTION; AES